The Role of Notaries in Drafting and Registering Online Fiduciary Security Deeds from the Perspective of Sharia Economic Law - Barokah , Tika Siti; Hafizd, Jefik Zulfikar (Aghnina : Jurnal Hukum Ekonomi Syari'ah, 2025)
Notaries play a crucial role in society, especially in drafting authentic deeds as required by statutory regulations. Law No. 2 of 2014, amending Law No. 30 of 2004 on the Notary Profession, grants notaries the authority to create authentic deeds to ensure legal certainty, order, and legal protection. This study formulates two main problems: the role of notaries in assisting creditors with the online registration of fiduciary security deeds and the supporting and inhibiting factors they encounter in this process. Employing a juridical-sociological approach with descriptive-analytical methods and purposive sampling for data collection, the study uses both primary and secondary data analyzed qualitatively. The findings show that, based on Law No. 42 of 1999 on Fiduciary Security, the registration of fiduciary security ensures legal certainty and protection for both grantors and recipients. It is further stipulated that fiduciary registration must be completed within 30 days of the notarial deed’s issuance, and the deed must be distinct from the principal agreement.